Seasonal Pattern of Diverticular Disease Admissions in Central Anatolia - Fatih Dal; Uğur Topal; Erdoğan Mütevelli Sözüer; Muhammet Akyüz; Tutkun Talih; İlker Büyükince (Turkish Journal of Colorectal Disease, 2021)

(untitled)
Aim:In the present study, we aimed to investigate the seasonal characteristics of presentations to the hospital due to diverticular disease.Method:The patients who were admitted to the hospital between January 1st, 2015 and January 1st, 2020 due to diverticular disease were included in the study. The study was designed retrospectively. The patients were divided into groups according to the treatment method, namely Group 1: patients who received surgical treatment, and Group 2: patients who received medical treatment. Age, sex and seasonal periods were compared. Also, the patients were separated into three groups according to age: those between 18 and 40 years of age, those between 40 and 60 of age and those over 60 years of age. The sex and the treatment methods of the patients were also examined in the season groupsResults:One hundred fifty seven patients participated in our study. Group 1 consisted of 39 patients and Group2 consisted of 118 patients. Presentations to the hospital with acute diverticulitis occurred most frequently in the winter (39.5%). The average age was higher in Group 1 (60.61 vs 54.42, p=0.030). The sex distribution was similar in the groups (p=0.152). Winter was dominant in treatment groups (30.8% vs 42.4% p=0.060). In winter, the average age of the patients who received surgical treatment was higher than those who received medical treatment (68 vs 50 p=0.001). In winter, all patients who received surgical treatment were over 60 years of age. In summer, the ratio of patients who received medical treatment was highest for the group over 60 years of age (p=0.040).Conclusion:In our study, we displayed the seasonal change in hospital admissions due to diverticular disease. We detected an increased rate of presentations to the hospital in winter. Selection of the treatment method did not display a seasonal variation. However, when we made an additional evaluation according to the age groups, it was seen that greater number of patients who were older than 60 years received surgical treatment in winter whereas the greater number of them received medical treatment in summer. Pathophysiological mechanism of this change could not be fully revealed.